KNOWLEDGE AND ATTITUDES TOWARD VOLUNTARY BLOOD DONATION AMONG FULL-TIME STUDENTS AT THAI BINH MEDICAL COLLEGE IN THE ACADEMIC YEAR 2025–2026 (Vietnam Journal of Community Medicine, 2026)
Objective: To assess knowledge and attitudes toward voluntary blood donation and identify related factors and barriers among full-time students at Thai Binh Medical College.Methods: A cross-sectional study with quantitative and qualitative components was conducted among 383 full-time students at Thai Binh Medical College from December 2025 to March 2026. Data were collected using a structured and pre-tested questionnaire. Quantitative data were analyzed using SPSS version 25.0 with descriptive and analytical statistics.Results: The mean age of participants was 19.4 ± 1.9 years, and 72.3% were female. Overall, 90.1% of participants had adequate knowledge regarding voluntary blood donation, with a mean knowledge score of 9.02 ± 1.82 points. Correct response rates were high for most common blood donation questions, particularly regarding minimum weight eligibility (89.3%), blood donation interval (85.9%), and transfusion-transmitted infections (95.8%). Positive attitudes toward voluntary blood donation were observed in 88.3% of participants, with a mean attitude score of 9.71 ± 2.82 points. Most participants were willing to donate blood voluntarily (86.2%) and support friends and relatives participating in blood donation activities (89.6%). Major barriers to blood donation were relatively low; however, 37.3% of participants reported lack of confidence regarding their eligibility for blood donation, and 20.1% considered blood donation procedures to be time-consuming.Conclusion: Students at Thai Binh Medical College demonstrated generally good knowledge and positive attitudes toward voluntary blood donation. Continued communication and educational interventions are needed to improve specific knowledge gaps and reduce barriers related to blood donation participation.
Keywords: Voluntary blood donation; knowledge; attitude; barriers; students; Vietnam.